Solubilization of protein of steam-heated defatted soybean meal by ultrasonication and some properties of the dissolved protein - Odajima, Y; Watanabe, T. (Kyoritsu Women's Univ., Tokyo (Japan)) (NIPPON SHOKUHIN KOGYO GAKKAISHI, 1986)
When steam-heated defatted soybean meal having low Protein Dispersibility Index (PDI) was ultrasonicated in water, a part of insolubilized protein became soluble again and thus the PDI was higher than that before ultrasonication. Protein molecules agglomerated by steam-heating were perhaps partly decomposed by ultrasonication resulting in solubilization in water. Similar to protein components of the normal water extract of unsteamed soybean meal, 7S and 11S protein were found by acrylamide gel electrophoresis to be the main components of the dissolved protein. When calcium chloride was added to the extract obtained by ultrasonication, the protein precipitated as cold or hot extract of unsteamed soybean meal and the precipitation ratio was much higher than that of hot extract of steam-heated soybean meal. In the case of soybean meal of very low PDI by high-temperature long-time steam-heating recovery of PDI by ultrasonication was fairly poor, perhaps for more stable intermolecular bonding of protein such as co-valent bonds. When water-soluble isolated soybean protein was steamed and then ultrasonicated in water, only a small part of protein became soluble. In this case closeness of protein molecules to each other and less amounts of accompanying non-protein impurities may be responsible for the stable intermolecular bonding.